(untitled) (Education in the 21st Century, 2023)
In recent years in methodological and pedagogical literature are often met works according to the necessity of modern technological based learning of the teaching subjects during the practical and seminar courses as well as in teaching process of various subjects in public school and in higher and vocational secondary education. As experience shows the specialists often confuse with each other the important terms such as "teaching technology", “Technology of education”, "pedagogical technology", "traditional teaching technology" and "computer technology". In this sense it is too important and actually targeted applications and corrections of the “traditional” and “Modern technologies” terms of the teaching as they create wide range of possibilities to improve the quality of the education as well as public and higher education coincidently to promote the development of the comparative pedagogy. Its necessity is important by the fact that since 2019-2020 academic year for the first time in Armenia by the initiative of the centre of the development of the pedagogy and education in the faculties of YSU. Its necessity is also highlighted by the fact that for the first time in 2019-20 academic year in Armenia, by the initiative of Pedagogy and Education Development Center in the faculties of YSU in last year of bachelor degree course is taught the subject "Educational Technologies". Thus, this article is devoted to define the content of the concepts of modern pedagogical and educational technologies, as well as to the comparative analysis of traditional and modern educational technologies.